Electrophoretic Deposition of Multi-Walled Carbon Nanotube Coatings on CoCrMo Alloy for Biomedical Applications - Bożena Łosiewicz; Patrycja Osak; Karolina Górka-Kulikowska (Micromachines, 2023)
Carbon nanotubes are a promising material for use in innovative biomedical solutions due to their unique chemical, mechanical, electrical, and magnetic properties. This work provides a method for the development of ultrasonically assisted electrophoretic deposition of multi-walled carbon nanotubes on a CoCrMo dental alloy. Functionalization of multi-walled carbon nanotubes was carried out by chemical oxidation in a mixture of nitric and sulfuric acids. The modified and unmodified multi-walled carbon nanotubes were anaphoretically deposited on the CoCrMo alloy in an aqueous solution. Chemical composition was studied by Fourier transform infrared spectroscopy. Surface morphology was examined by scanning electron microscopy. The mechanism and kinetics of the electrochemical corrosion of the obtained coatings in artificial saliva at 37 °C were determined using the open-circuit potential method, electrochemical impedance spectroscopy, and anodic polarization curves. The capacitive behavior and high corrosion resistance of the tested electrodes were revealed. It was found that the kinetics of electrochemical corrosion of the CoCrMo electrode significantly decreased in the presence of the functionalized multi-walled carbon nanotube coating. Electrophoretic deposition was shown to be an effective, low-cost, and fast method of producing nanotubes with controlled thickness, homogeneity, and packing density.